Association of gestational diabetes mellitus with vitamin D status among women attending at Bangabandhu Sheikh Mujib Medical University: Association of gestational diabetes mellitus with vitamin D (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Gestational diabetes mellitus (GDM) is an important cause of maternal and perinatal morbidities. Vitamin D is associated with glucose metabolism. The present study was aimed to assess the association of maternal serum vitamin D level with GDM. This case-control study was conducted among 80 pregnant women at the Department of Obstetrics and Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Among the 80 patients, 40 were GDM patients (cases) and 40 pregnant women without GDM (controls). The serum vitamin D level was measured for all of them. The mean vitamin D level of the cases and controls were 18.8±5.5 ng/ ml and 22.1±7.3 ng/ml, respectively (P=0.025). There was significant difference regarding the vitamin D adequacy in between case and control groups (P= 0.006) and the respondents with vitamin D